Kampanye Public Relations dalam Mensosialisasikan Penyalahgunaan Narkoba : Siswa SMK Bina Husada Mandiri Bekasi - Bintang Nurijadi; Novida Irawan; Yeni Yustianingsih (MUKASI: Jurnal Ilmu Komunikasi, 2024)
Public Relations campaign is a means of activity carried out by the Indonesian government as an information event for the community. Forza Anti Napza Youth Forum (FORZA) Indonesia is one of the organizations that conducts campaign activities aimed at providing information and knowledge to high school students about the dangers of drug abuse. The purpose of the research is to find out the Public Relations campaign carried out in socializing drug abuse among students of SMK Bina Husada Mandiri Bekasi City. The research method is a qualitative approach. The collection technique is primary data in the form of interviews and secondary data in the form of documentation. The results of the study showed that: (1) Offline media in the form of exposure in the form of slides inserted with videos or short animated films and online media in the form of Instagram and YouTube official Forza. (2) Obstacles in conducting campaigns are lack of preparation and external obstacles in the form of threatening SMS or mugging on the toll road. (3) Forza conducts campaigns with two communication strategies, namely face-to-face communication in the form of direct programs to schools, and universities, and collaboration with communities and online communication such as in this pandemic era Forza maximizes webinars.